MCTS self-paced training kit (Exam 70-680) : configuring Windows 7 - McLean, Ian (Microsoft Press WashingtonUS, 2010)
Provides information on installing and migrating to Windows 7; deploying Windows 7, configuring hardware and applications, network connectivity, access to resources and mobile computing, and backup and recovery options. Includes data on monitoring and maintaining systems that run Windows 7.